Pembuatan Surat Kuasa Membebankan Hak Tanggungan (SKMHT) Pada Pengalihan Hutang Kredit Di PT. BRI Agro Cabang Pekanbaru - Bayu Nofyandri Surbakti; Yulfasni Yulfasni; Syahrial Razak (Nagari Law Review, 2018)
The collateral is one of most important the elements in facilitating loan by a bank, no matter how other elements have been able to convince the bank against security and legal certainty in the credit repayment that. In practice, collateral factor is also important in the valuation of the credit value released, because the credit disbursed by the bank contains risks. Letter of authority to charge Mortgage (SKMHT)n is a power granted by the party to charge a person special authority to charge an object especially land with mortgage. Notary has the authority to make SKMHT for the lands throughout the territory of Indonesia, while Land Deed Making Officer (PPAT) may only make SKMHT for lands within its permitted territorial, especially in places where there is no Notary in charge. SKMHT formation other than by a Notary is also assigned to PPAT, because PPAT which its existence depend on the area where he permitted by regulation related to his function and duty on land affair. SKMHT basically does not contain other legal acts either in the form of selling, renting the object of mortgage right, as it is regulated in Article 15 paragraph (1) of the Mortgage Act. Therefore, it can be said that SKMHT is not a guarantee, but as an early effort for the debtor to provide confidence to the bank, that the debtor has good faith in the credit agreement by granting power to the bank to increase the position of land used for collateral to the Deed of Assignment Rights.